On the Need to Compare the Architecture Design of Large Language Models: A Preliminary Reference Metamodel - Carreño-Bolufer, Jesús; Giachetti, Giovanni (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2026.42481, 2026)
A large number of Large Language Models (LLMs) have been developed and made available to the community. However, analyzing and comparing these models remains challenging since there is no clear, standardized way to describe their architectures precisely. While LLM developers typically provide textual model cards, configuration files, or source code, these artifacts do not follow a common standard. Consequently, researchers need to make additional efforts to reuse and compare existing LLMs. To address this issue, we propose a conceptual modeling approach to create a model-driven method for describing and analyzing LLM architectures.